Pengaruh Kepercayaan dan Kualitas Pelayanan terhadap Kepuasan Pasien Rawat Jalan dan Implikasinya terhadap Loyalitas Pasien Rawat Jalan di RSUD Tgk. Di Tiro Sigli - Agustina, Mona; Ibrahim, Ibrahim; Abqa, Rizkan (Singkite Journal, 2024)
The relationship between trust and quality of patient service has an impact on patient satisfaction, and this has implications for their loyalty in using and recommending the Hospital. This will be proven by this study. Using a sample of 325 outpatients, an inferential test was conducted quantitatively with path analysis. The results found that; 1) there is a direct and indirect influence of patient trust on satisfaction, through the service quality variable, of 25.13%. 2) there is a direct and indirect influence of service quality on patient satisfaction, through the patient trust variable, of 23.59%. 3) Simultaneously, patient trust and service quality affect patient satisfaction. 4) there is a direct and indirect influence of patient trust on patient loyalty, through the service quality variable, of 37.78%. 5) there is a direct and indirect influence of service quality on patient loyalty, through the patient trust variable of 25.4%. 6) The total influence of patient trust and service quality on patient loyalty, through the patient satisfaction variable, is 17.61%.